Fiz de coração: mapeamento de mensagens de amor - PEÇANHA, Lygia Cardoso (2024)
The role of love letters in the history of Western literature is fundamental, as it allows us to reflect on the practices of personal writing in the context of cultural exchanges, social relationships, performativity, and expressions of love. With the advent of new technologies, other means of communication have emerged, such as radio, telephone, and car telemessage services, as well as urban interventions like graffiti and banners with messages, which also incorporate aspects of epistolary love writing. In this context, this dissertation, titled "From the Heart: Mapping Contemporary Love Messages," aims to conduct an interdisciplinary research on mapping contemporary love messages, exploring their expressive and performative potential. The methodology employed includes the research-action method, structured in two phases: an information gathering phase and a field research phase, in which a collaborative experience is conducted to activate the investigated media. The research establishes connections with the contemporary artworks of artists Camila Buzelin (2009) and Juraci Dórea (1989). It also involves a literature review addressing perspectives on love in both public and private contexts, aspects of the material and social dimensions of epistolary writing, and the gesture of intimate addressing. In the field phase, data is collected through participant observation, with graphic and audio recording of conversations and artistic products stemming from a collaborative experience with the #Joyces collective (2023). This aims to construct a critical interpretation of the possible interactions of love correspondence, its shifts in content, and the formal modifications caused by the mapped media.